2015
DOI: 10.1007/s11356-015-5267-z
|View full text |Cite
|
Sign up to set email alerts
|

Screening of phthalate esters in 47 branded perfumes

Abstract: In the last few years, the use of phthalates in perfumes has gained attention because these chemicals are sometimes added intentionally as a solvent and a fixative. Five phthalate esters, dimethyl phthalate (DMP), diethyl phthalate (DEP), dibutyl phthalate (DBP), benzyl butyl phthalate (BBP), and diethyl hexyl phthalate (DEHP), were measured in 47 branded perfumes using headspace solid phase microextraction (SPME) followed by gas chromatography-mass spectrometry (GC-MS). The results revealed considerable amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
24
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(31 citation statements)
references
References 40 publications
2
24
5
Order By: Relevance
“…Of significance, however, is the fact that the manufacturer lists the composition of the aqueous gel product used at MGH obstetrical unit to include: propylparaben, fragrance, and dyes among the ingredients. It is possible that DBP and BBzP compounds are used in the gel product as solvents/fixatives to adhere fragrance and/or color/dye to the gel (Al-Saleh and Elkhatib 2016) and that urinary increases at 8.6 hours post-ultrasound reflect dermal absorption of the product at time of ultrasound imaging. However, it is also possible that observed concentration increases at time 3 also reflect additional exposure through food, cosmetics, and other sources including potential hospital procedures following ultrasound.…”
Section: Discussionmentioning
confidence: 99%
“…Of significance, however, is the fact that the manufacturer lists the composition of the aqueous gel product used at MGH obstetrical unit to include: propylparaben, fragrance, and dyes among the ingredients. It is possible that DBP and BBzP compounds are used in the gel product as solvents/fixatives to adhere fragrance and/or color/dye to the gel (Al-Saleh and Elkhatib 2016) and that urinary increases at 8.6 hours post-ultrasound reflect dermal absorption of the product at time of ultrasound imaging. However, it is also possible that observed concentration increases at time 3 also reflect additional exposure through food, cosmetics, and other sources including potential hospital procedures following ultrasound.…”
Section: Discussionmentioning
confidence: 99%
“…In context, alterations in physical activity by common environmental endocrine disruptors, such as BBP, is important because BBP is ubiquitous in cosmetics and personal care products used daily by most people, especially by women (1, 12, 16, 40). To our knowledge, this is the first data to suggest that a common endocrine disruptor can significantly inhibit physical activity in offspring.…”
Section: Discussionmentioning
confidence: 99%
“…9,[14][15][16][17][18][19][20][21][22][23][24][25][26][27] The most commonly used technique for the determination of PEs in perfumes is gas chromatography -mass spectrometry (GC-MS) e.g. 9,18,19,[28][29][30][31] Several studies have reported the presence PEs in perfumes in wide concentration ranges from sub ppm to high percentage. 31,32 Therefore a preconcentration step is usually required in order to determine PEs at sub ppm levels.…”
mentioning
confidence: 99%
“…9,18,19,[28][29][30][31] Several studies have reported the presence PEs in perfumes in wide concentration ranges from sub ppm to high percentage. 31,32 Therefore a preconcentration step is usually required in order to determine PEs at sub ppm levels.…”
mentioning
confidence: 99%
See 1 more Smart Citation